Effects of corn particle size, complete diet grinding, and diet form on finishing pig growth performance, caloric efficiency, carcass characteristics, and economics - J A De Jong; Michael D Tokach; Leland J McKinney; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 855 pigs (PIC TR4 × Fast Genetics York × PIC Line 02), initially 56.54 lb BW) were used in a 111-d trial to evaluate the effects of corn particle size, complete diet grinding, and diet form (meal or pellet) on finishing pig growth performance, caloric efficiency, carcass characteristics, and economics. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 5 dietary treatments with 9 replications per treatment. The same corn-soybean meal—based diets containing 30% dried distillers grains with solubles (DDGS) and 20% wheat middlings (midds) were used for all treatments. Diets were fed in four phases. Different processing techniques were used to create the 5 dietary treatments: (1) roller grinding the corn to approximately 650 Î¼ with the diet fed in meal form; (2) hammer-mill grinding the corn to approximately 320 Î¼ with the diet fed in meal form; (3) Treatment 2 but pelleted; (4) corn initially roller-mill ground to approximately 650 Î¼, then the complete mixed diet reground through a hammer mill to approximately 360 Î¼ with the diet fed in meal form; and (5) Treatment 4 but pelleted. Overall (d 0 to 111), reducing corn particle size from approximately 650 to 320 Î¼ improved (P<0.03) F/G, caloric efficiency, feed cost per lb of gain, and income over feed cost (IOFC). Grinding the complete diet decreased ADG, ADFI, and final weight when the diet was fed in meal form, but increased performance when fed in pelleted form resulting in diet form × portion ground interactions (P<0.02). Pelleting the diet improved (P<0.001) ADG, F/G, caloric efficiency on an ME and NE basis, final weight, carcass weight, and IOFC.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Finishing pig; Ingredient processing; Particle size; Pellet